2022
DOI: 10.1002/cae.22571
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of web‐based extended reality technologies for physics education

Abstract: Extended reality (XR) technologies such as augmented reality (AR) and virtual reality (VR) are being increasingly used for education and skill development through the development of interactive learning environments (ILEs) with XR implementations. For physics education, these ILEs with XR are capable of improving the visual representation of educational content, as well as stimulating the cognitive process of learning with interactive experiences. In this study, we focused on evaluating students' perceptions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…However, the impact of activities in AR mode on student motivation to learn was greater than in VR mode. With this respect, the results of Zatarain-Cabada et al (2023) are similar to those of the present study. The earlier studies and the present study suggested that well-designed learning tools, including extended reality, can greatly impact a learner's performance.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the impact of activities in AR mode on student motivation to learn was greater than in VR mode. With this respect, the results of Zatarain-Cabada et al (2023) are similar to those of the present study. The earlier studies and the present study suggested that well-designed learning tools, including extended reality, can greatly impact a learner's performance.…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that the XR technologies used in this study helped to improve students' learning perception and performance because it is important to point out that these technologies motivate students and make them maintain attention to the subject matter (Zatarain-Cabada et al, 2023). As indicated by Zatarain-Cabada et al (2023), the significance of developing specific educational materials, including the arrangement of the learning space, the execution of effective instructional exercises, and the precision and excellence of instructional materials are important for increasing students' perceptions. These factors significantly impact the level of learning and performance achieved by learners.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The VOS Viewer offers bibliometric analysis mapping with three different visualizations, including the overlay visualization mentioned (see Figure 12). Based on Figure 12, Augmented Reality research is more related to clinical articles (Jeffers et al, 2022;Lau et al, 2023), extended reality (Chang et al, 2023;Gurses et al, 2023;Spadoni et al, 2022), likert scale (Soyka & Simons, 2022;Zatarain-Cabada et al, 2023), and nuclear magnetic resonance imaging (De Benedictis et al, 2023;Shahbaz et al, 2023). Additionally, Augmented Reality research is applied from early childhood education to higher education levels (Senduk et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Another advance in this area is the release of a range of graphics-oriented libraries that enable high level, platform agnostic development of interactive web-based applications that make use of graphics processing units (GPUs) to do large-scale calculations in real time (Angel and Shreiner 2014), typically targeting 2D and 3D graphics. Libraries based on the popular WebGL framework include Three.js (Dirksen 2013), Babylon.js (Catuhe et al 2014) and Abubu.js (Kaboudian et al 2019a), which each allow for high-level interaction with GPUs within the context of a webpage and have been used in a variety of physics education scenarios (McCauley 2017;Zatarain-Cabada et al 2023). Abubu.js in particular has been used to develop a range of mathematical visualisations, with a particular focus on models of cardiac electrophysiology (Kaboudian et al 2021(Kaboudian et al , 2019b.…”
Section: Historical and Pedagogical Contextmentioning
confidence: 99%